APLIKASI ACTIVITY-BASED COSTING PADA UMKM - Himawan Pradipta (LP2M Universitas Ibrahimy, 2021)
The fact that there was a challenge for the UMKM sector was the lack of capability in terms of business menegement. One of them was accuracy in calculating the amount of the main price of production on the resulting product. even though that calculation was crucial in determining the selling price of the product. Therefore, it was important to apply a better method to make the right decision. The purpose of this study was to analyze the comparison of the calculation of the price of production using traditional costing (TC) and Activity-Based Costing (ABC) methods, as well as analyzed the advantage in gaining the application of this method. This research was a descriptive qualitative study with interview methods and documentation. The analysis showed that in the calculation of the underlying price between TC production and ABC, there was an undercosted of 4.04%, while for the profit difference there was 1.2%.